Studies on Threat Status of Tree species of Madhya Pradesh, India - Khanna, K. K.; Dubey, P. C.; Tiwari, A. P.; Sikarwar, R. L. S. (Indian Forester, 2021)
The present paper deals with the threat status of tree species of Madhya Pradesh as per IUCN criteria version 3.1 (2001). A total number of 40 species belonging to 24 families are reported under various threatened categories of IUCN in the present work. Out of 40 threatened species, 2 species are 'Critically Endangered', 6 species 'Endangered', 11 species 'Vulnerable' and 21 species 'Near Threatened'. The causes of threat have been discussed, and it has been observed that habitat loss due to various factors is the major cause of threat followed by unsustainable harvesting, lack of pollinators, diseases, edaphic factors and economic activities.